1983
DOI: 10.1002/ana.410130315
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral emboli of paradoxical origin

Abstract: A diagnosis of paradoxical cerebral embolus (PCE) was made in five patients aged 31 to 62 years who sustained eight cerebral ischemic events. No patient had evidence of primary carotid system or left heart disease. A probe-patent foramen ovale was the presumed mechanism in four patients, and an unsuspected congenital atrial septal defect was found in the fifth patient. Clinically apparent pulmonary emboli or venous thrombosis preceded the cerebral event in only one instance. Review of the literature reveals a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 41 publications
1
48
0
2
Order By: Relevance
“…6,8,19 These include obesity, index stroke severity, a history of deep venous thrombosis or pulmonary embolism, hypercoagulable states, prolonged travel/forced immobility, migraine, Valsalva at stroke onset, and "wake up" stroke/TIA. 20 Thus, further improvement in stratification and discrimination may be possible. Finally, because our approach was based on a model predicting PFO as an outcome, it was not possible to examine PFO characteristics (such as shunt size).…”
Section: Discussionmentioning
confidence: 99%
“…6,8,19 These include obesity, index stroke severity, a history of deep venous thrombosis or pulmonary embolism, hypercoagulable states, prolonged travel/forced immobility, migraine, Valsalva at stroke onset, and "wake up" stroke/TIA. 20 Thus, further improvement in stratification and discrimination may be possible. Finally, because our approach was based on a model predicting PFO as an outcome, it was not possible to examine PFO characteristics (such as shunt size).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Patent foramen ovale (PFO), a frequent finding in the general population, 4,5 is considered a possible underlying mechanism in a proportion of embolic stroke of undetermined source patients, 6 and its closure has been suggested as an efficacious intervention on top of medical treatment. Until recently, only 3 randomized controlled trials had tested this hypothesis yielding inconclusive results.…”
mentioning
confidence: 99%
“…Not long after Cohnheim's report, Zahn [3] reported a case in which necropsy revealed thrombosis in the iliac and uterine veins, multiple systemic emboli, and a thrombus lying in the foramen ovale. Since then, a number of cases of paradoxical embolism, often with a thrombus 'caught redhanded' in its passage through a PFO, have been reported, but this disorder has been considered a rare cause of stroke, with few cases diagnosed premortem [4][5][6][7][8],Interest in paradoxical embolism has recently been rekindled by the advent of contrast echocardiography which has proved to be a noninvasive and reliable tool for the detection of small right-to-left shunts presumed to be PFO in most cases [9]. In this respect, the recently introduced transesophageal contrast echocardiography appears to be more sensitive than the transthoracic approach [10].…”
mentioning
confidence: 99%
“…The clinical diagnosis of paradoxical embolism is usually a presumptive one, resting upon the following criteria [6,7]: (1) arterial embolism with no evidence of left-sided circulation source; (2) potential for right-to-left shunting (usually through a PFO); (3) venous thrombosis and/or pulmonary embolism (which is evidence of the presence of venous thrombosis and in addition confirms that embolization has occurred); (4) elevation of the right heart pressure (sustained as during pulmonary hyperten sion or transitory as during cough or Valsalva maneu ver). A sustained elevation of the right heart pressure, usually due to pulmonary embolism, is no longer consid ered a precondition for paradoxical embolism, since con trast echocardiography has clearly demonstrated that the normal interatrial left-to-right pressure gradient can be transiently reversed either spontaneously during early systole or by Valsalva-inducing activities such as cough ing [9].…”
mentioning
confidence: 99%